Features of University Teachers’ Communicative-Speaking Competence - Olga Korniyaka (Психолінгвістика, 2018)
The article clarifies the specifics and peculiarities of communicative-speaking competence as the key tool of university teachers’ professional communication. The empirical research revealing development of speech communicative means and their influence on professional self-fulfilment is summarised.